Preparation method of zero-valent iron reduction material with micro-nano size and water stability
Through the coordinated method of mechanical ball milling and cetyl trimethoxysilane surface modification, micro-nano zero-valent iron materials with high effluent stability and strong activity to degrade pollutants were prepared, which solved the problem of easy agglomeration and easy deactivation of micro-nano zero-valent iron, and achieved long-term and efficient pollutant repair effect.
Patent Information
- Application Number
- CN202411757538.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
Micro-nano zero-valent iron is easily agglomerated, easily deactivated, and difficult to store for a long time, resulting in a decrease in its degradation activity on pollutants. Frequent material replacement will reduce repair efficiency and increase costs.
Zerovalent iron reduction materials with micro-nano size and water stability were prepared by a synergistic method of mechanical ball milling and cetyltrimethoxysilane surface modification. This method performs mechanical ball milling through a ball mill and uses cetyl trimethoxysilane as a surface modifier to inhibit the agglomeration of micro-nano zero-valent iron and enhance its surface hydrophobicity and electron selectivity.
The prepared micro-nano zero-valent iron material maintains long-term stability in water, avoids agglomeration, and its reduction and degradation activity on halogenated hydrocarbons and heavy metals is significantly improved, which can maintain efficient pollutant repair capabilities for a long time, and reduces the frequency and cost of material replacement.
Smart Images

Figure CN119566321A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of groundwater halogenated hydrocarbon and heavy metal pollution remediation, and in particular to a method for preparing a zero-valent iron reduction material with micro-nano size and water stability. Background Art
[0002] Zero-valent iron is a highly active reducing material and is environmentally friendly. It can be used to treat halogenated hydrocarbons and heavy metal pollution in groundwater. Zero-valent iron can be prepared by liquid or solid phase chemical reduction of iron salts, or by mechanical ball milling of iron filings or iron powder. The particle size of zero-valent iron prepared by chemical reduction can be as small as nanometers, and it has high reduction activity, but it is extremely unstable in water (easy to agglomerate and passivate), and the preparation process is complex and costly, which greatly limits its application in practical engineering. The particle size of zero-valent iron prepared by mechanical ball milling can be as small as micrometers. Although its reduction activity is lower than that of nano zero-valent iron, it is more stable than nano zero-valent iron in water, and the preparation process is simple, cost-effective, and easy to achieve mass production, which has greater application prospects in practical engineering.
[0003] Zero-valent iron can be used as a reductively active material in a permeable reactive barrier (PRB) for groundwater pollution remediation. Before being used in actual projects, zero-valent iron generally undergoes a long period of water phase storage and transportation. The particle size of micro-nano zero-valent iron (100-1000nm) is larger than that of nano zero-valent iron, and its degradation activity for pollutants is relatively low. In order to ensure sufficient pollutant remediation efficiency, it is necessary to focus on the degradation activity of micro-nano zero-valent iron during actual storage, transportation and use; when the activity decreases, the material needs to be replaced. However, frequent replacement of zero-valent iron materials will reduce the remediation efficiency and increase the remediation cost. Although the size of micro-nano zero-valent iron is larger than that of nano zero-valent iron, it is still easy to agglomerate in water and easily react with water molecules, which further reduces its reductive degradation activity for pollutants. Therefore, it is urgent to develop a micro-nano zero-valent iron preparation technology that is stable in water for a long time and has a low reductive activity, so as to realize the micro-nanoization of zero-valent iron and solve the technical problems of easy deactivation and difficult storage of micro-nano zero-valent iron, thereby improving the remediation efficiency, reducing the remediation cost, and shortening the pollution control cycle.
[0004] In order to solve this problem, modification methods for micro-nano zero-valent iron, such as surface modification with oxygen-containing acid radicals, have been proposed in the prior art. However, although the surface modification method with oxygen-containing acid radicals solves the agglomeration problem to a certain extent, it cannot effectively inhibit the side reactions between micro-nano zero-valent iron and water molecules, that is, it cannot improve the water stability of micro-nano zero-valent iron; after long-term use, its degradation activity for pollutants will quickly decrease. In addition, the commonly used hydrophobic modification technology based on post-synthesis adsorption loading can improve the stability of micro-nano zero-valent iron in water, but it will greatly reduce its reaction activity and cannot meet the needs of actual engineering applications. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a zero-valent iron reduction material with micro-nano size and water stability. The method provided by the present invention is expected to solve the problem that micro-nano zero-valent iron is easy to agglomerate, easy to deactivate, and difficult to store for a long time in water.
[0006] To solve the technical problem, on the one hand, the present invention provides a method for preparing a zero-valent iron reduction material with micro-nano size and water stability, comprising the following steps:
[0007] 1) Mix the micron-sized zero-valent iron powder and the surface modifier, and perform mechanical ball milling using a ball mill;
[0008] 2) Cleaning the material after ball milling in step 1) with a cleaning agent and drying it to obtain the zero-valent iron reduction material with micro-nano size and water stability.
[0009] The micron-sized zero-valent iron powder is a reduced iron powder with a particle size range of 100 to 200 meshes. The mass ratio of the micron-sized zero-valent iron powder to hexadecyltrimethoxysilane is 2:1 to 160:1. After the mechanical ball milling, the average particle size of the material is 269.0 to 527.5 nm. The mechanical ball milling is carried out using a ball mill, the ball milling speed is 400 to 500 rpm, and the ball milling time is 12 to 24 hours. The cleaning agent is anhydrous ethanol. The vacuum drying temperature is 60 to 80°C, and the time is 12 to 24 hours.
[0010] In a second aspect, the present invention provides a zero-valent iron reduction material having micro-nano size and water stability prepared by the aforementioned method.
[0011] In a third aspect, the present invention also provides the use of the surface modified micro-nano zero-valent iron as a reducing agent in the degradation of halogenated hydrocarbons or heavy metal pollutants in water, preferably, especially for the degradation of trichloroethylene or hexavalent chromium in water.
[0012] The present invention creatively discovered that hexadecyltrimethoxysilane has the ability to inhibit the aggregation of micro-nano zero-valent iron and improve its surface hydrophobicity and electron selectivity. The present invention prepared a micro-nano zero-valent iron reduction material through a synergistic method of mechanical ball milling and hexadecyltrimethoxysilane surface modification. Because hexadecyltrimethoxysilane contains hydrophobic groups, the obtained material has good water stability and can avoid the aggregation of the material in water; more importantly, hexadecyltrimethoxysilane has electron selectivity, and can also be used as a ball milling aid to promote the rupture of iron powder particles during the ball milling process, prevent cold welding of iron powder particles, and reduce the size of micro-nano zero-valent iron particles, thereby improving the activity of micro-nano zero-valent iron, making it have stronger reaction activity to pollutants than blank micro-nano zero-valent iron; in addition, long-term (60 days) application tests show that the micro-nano zero-valent iron prepared by mechanical ball milling and hexadecyltrimethoxysilane surface modification can always maintain a high reduction activity to halogenated hydrocarbons and heavy metals in water. Therefore, this method can not only improve the reduction and degradation activity of micro-nano zero-valent iron materials on halogenated hydrocarbons and heavy metals, but also maintain the reduction activity of the materials in water for a long time, so that it can be used in the remediation of halogenated hydrocarbons and heavy metal pollutants in groundwater for a long time, reducing the consumption of material resources. The materials used in the present invention are all cheap and readily available materials, the preparation method is simple, the cost is low, and it can be mass-produced, and it has good economic and environmental benefits in practical applications.
[0013] The surface modified micro-nano zero-valent iron obtained by the micro-nano zero-valent iron surface modification method developed by the present invention has good reduction performance for trichloroethylene and hexavalent chromium. In the same reaction cycle, the removal rates of trichloroethylene and hexavalent chromium are increased by 189.5% and 71.8% respectively.
[0014] The surface-modified micro-nano zero-valent iron obtained by the micro-nano zero-valent iron surface modification method developed by the present invention has good water stability. After 60 days of immersion in water, the zero-valent iron content of the material is only reduced by 14.0%, and the removal capacity of trichloroethylene and hexavalent chromium can be maintained at more than 90%, solving the problem of easy deactivation and difficult storage of micro-nano zero-valent iron.
[0015] The surface modified micro-nano zero-valent iron developed by the present invention has a simple preparation process and can be mass-produced through a ball milling process. It is an efficient, green and low-cost method for stabilizing zero-valent iron. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The degradation rate of trichloroethylene (14 days) of ball-milled iron powder and surface-modified micro-nano zero-valent iron materials in various proportions before and after immersion in water (60 days) according to the present invention;
[0017] Figure 2 The degradation rate of hexavalent chromium (24h) by ball-milled iron powder and surface-modified micro-nano zero-valent iron materials in various proportions before and after immersion in water (60 days) according to the present invention;
[0018] Figure 3 The present invention relates to the zero-valent iron content of ball-milled iron powder before and after immersion in water (60 days) and surface-modified micro-nano zero-valent iron materials in various proportions. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with preferred embodiments.
[0020] Each embodiment uses a hydrogen production test to test the zero-valent iron content of the material. The hydrogen production test process is as follows: 2 mg of surface-modified micro-nano zero-valent iron material is added to 10 mL of a 6 mol / L sulfuric acid aqueous solution, and the reaction is complete for 24 hours under closed conditions. The headspace sample is taken to determine the generated H2 content, and the zero-valent iron content is calculated using a chemical reaction equation. In the embodiment, the removal rate = 100% × (initial pollutant mass concentration - pollutant mass concentration after degradation) / initial pollutant mass concentration.
[0021] In each embodiment, the reduced iron powder is 100 mesh commercially available reduced iron powder. The ball mill is a QM-3SP2 planetary ball mill. The remaining reagents or materials in the embodiments are all commercially available reagents.
[0022] Example 1 Preparation of surface modified micro-nano zero-valent iron material and its application in the degradation of trichloroethylene
[0023] 5g of reduced iron powder and 31.25mg of hexadecyltrimethoxysilane were mixed evenly in a 50ml ball mill, and placed in a QM-3SP2 planetary ball mill for ball milling at 450rpm for 24h. The material was washed with anhydrous ethanol and vacuum dried for 12h to obtain a surface-modified micro-nano zero-valent iron material (0.625% PSO-ZVI). Scanning electron microscope (SEM) images showed that the particle size of the material was 320.1±6.3nm, and the results of hydrogen production experiments showed that the zero-valent iron content of the material was 98.8%. 76.5mg of the material was added to 21.5mL of an aqueous solution containing 10mg / L trichloroethylene and reacted under anaerobic conditions for 14 days. The removal rate of trichloroethylene by the material reached 90.1%. After the material was immersed in water for 60 days, the zero-valent iron content became 85.1%, a decrease of only 13.9%; under the same conditions, its removal rate of trichloroethylene became 88.3%, a decrease of only 2.0%. Therefore, the 0.625% PSO-ZVI reducing material has good water stability and can maintain the reduction activity of trichloroethylene for a long time.
[0024] Example 2 Preparation of surface modified micro-nano zero-valent iron material and its application in the degradation of trichloroethylene
[0025] 5g of reduced iron powder and 0.25g of hexadecyltrimethoxysilane were mixed evenly in a 50ml ball mill, and placed in a planetary ball mill for ball milling at 450rpm for 24h. The material was washed with anhydrous ethanol and vacuum dried for 12h to obtain a surface-modified micro-nano zero-valent iron material (5% PSO-ZVI). Scanning electron microscope (SEM) images showed that the particle size of the material was 269.0±23.5nm, and the results of the hydrogen production experiment showed that the zero-valent iron content of the material was 95.9%. 76.5mg of the material was added to 21.5mL of an aqueous solution containing 10mg / L trichloroethylene and reacted under anaerobic conditions for 14 days. The removal rate of trichloroethylene by the material reached 99.9%. After the material was immersed in water for 60 days, the zero-valent iron content became 82.5%, a decrease of only 14.0%; under the same conditions, its removal rate of trichloroethylene became 99.8%, a decrease of only 0.1%. Therefore, the 5% PSO-ZVI reducing material has good water stability and can maintain the reduction activity of trichloroethylene for a long time.
[0026] Example 3 Preparation of surface modified micro-nano zero-valent iron material and its application in the degradation of trichloroethylene
[0027] 5g of reduced iron powder and 0.5g of hexadecyltrimethoxysilane were mixed evenly in a 50ml ball mill, and placed in a planetary ball mill for 24h at 450rpm. The material was washed with anhydrous ethanol and vacuum dried for 12h to obtain a surface-modified micro-nano zero-valent iron material (10% PSO-ZVI). Scanning electron microscope (SEM) images showed that the particle size of the material was 292.4±23.0nm, and the results of the hydrogen production experiment showed that the zero-valent iron content of the material was 96.7%. 76.5mg of the material was added to 21.5mL of an aqueous solution containing 10mg / L trichloroethylene and reacted under anaerobic conditions for 14 days. The removal rate of trichloroethylene by the material reached 97.4%. After the material was immersed in water for 60 days, the zero-valent iron content became 84.6%, and the decrease ratio was only 12.5%; under the same conditions, its removal rate of trichloroethylene became 99.6%, and the increase ratio was 2.3%. Therefore, the 10% PSO-ZVI reduction material has good water stability and can maintain the reduction activity of trichloroethylene for a long time.
[0028] Example 4 Preparation of surface modified micro-nano zero-valent iron material and its application in the degradation of trichloroethylene
[0029] 5g of reduced iron powder and 2.5g of hexadecyltrimethoxysilane were mixed evenly in a 50ml ball mill, and placed in a planetary ball mill for 24h at 450rpm. The material was washed with anhydrous ethanol and vacuum dried for 12h to obtain a surface-modified micro-nano zero-valent iron material (50% PSO-ZVI). Scanning electron microscope (SEM) images showed that the particle size of the material was 527.5±49.1nm, and the results of the hydrogen production experiment showed that the zero-valent iron content of the material was 85.0%. 76.5mg of the material was added to 21.5mL of an aqueous solution containing 10mg / L trichloroethylene and reacted under anaerobic conditions for 14 days. The removal rate of trichloroethylene by the material reached 73.6%. After the material was immersed in water for 60 days, the zero-valent iron content became 74.9%, and the decrease ratio was only 11.9%; under the same conditions, its removal rate of trichloroethylene became 83.4%, and the increase ratio was 13.3%. Therefore, the 50% PSO-ZVI reduction material has good water stability and can maintain the reduction activity of trichloroethylene for a long time.
[0030] Example 5 Preparation of surface modified micro-nano zero-valent iron material and its application in the degradation of hexavalent chromium
[0031] 5g of reduced iron powder and 31.25mg of hexadecyltrimethoxysilane were mixed evenly in a 50ml ball mill, and placed in a planetary ball mill for 24h at 450rpm. The material was washed with anhydrous ethanol and vacuum dried for 12h to obtain a surface-modified micro-nano zero-valent iron material (0.625% PSO-ZVI). Scanning electron microscope (SEM) images showed that the particle size of the material was 320.1±6.3nm, and the results of the hydrogen production experiment showed that the zero-valent iron content of the material was 98.8%. 76.5mg of the material was added to 21.5mL of an aqueous solution containing 20mg / L hexavalent chromium and reacted for 24h under anaerobic conditions. The removal rate of hexavalent chromium by the material reached 87.3%. After the material was immersed in water for 60 days, the zero-valent iron content became 85.1%, and the decrease ratio was only 13.9%; under the same conditions, its removal rate of hexavalent chromium became 99.9%, and the increase ratio was 14.4%. Therefore, the 0.625% PSO-ZVI reducing material has good water stability and can maintain the reducing activity of hexavalent chromium for a long time.
[0032] Example 6 Preparation of surface modified micro-nano zero-valent iron material and its application in the degradation of hexavalent chromium
[0033] 5g of reduced iron powder and 0.25g of hexadecyltrimethoxysilane were mixed evenly in a 50ml ball mill, and placed in a planetary ball mill for ball milling at 450rpm for 24h. The material was washed with anhydrous ethanol and vacuum dried for 12h to obtain a surface-modified micro-nano zero-valent iron material (5% PSO-ZVI). Scanning electron microscope (SEM) images showed that the particle size of the material was 269.0±23.5nm, and the results of the hydrogen production experiment showed that the zero-valent iron content of the material was 95.9%. 76.5mg of the material was added to 21.5mL of an aqueous solution containing 20mg / L hexavalent chromium and reacted for 24h under anaerobic conditions. The removal rate of hexavalent chromium by the material reached 99.5%. After the material was immersed in water for 60 days, the zero-valent iron content became 82.5%, and the decrease ratio was only 14.0%; under the same conditions, its removal rate of hexavalent chromium became 99.9%, and the increase ratio was 0.4%. Therefore, the 5% PSO-ZVI reducing material has good water stability and can maintain the reducing activity of hexavalent chromium for a long time.
[0034] Example 7 Preparation of surface modified micro-nano zero-valent iron material and its application in the degradation of hexavalent chromium
[0035] 5g of reduced iron powder and 0.5g of hexadecyltrimethoxysilane were mixed evenly in a 50ml ball mill, and placed in a planetary ball mill for 24h at 450rpm. The material was washed with anhydrous ethanol and vacuum dried for 12h to obtain a surface-modified micro-nano zero-valent iron material (10% PSO-ZVI). Scanning electron microscope (SEM) images showed that the particle size of the material was 292.4±23.0nm, and the results of the hydrogen production experiment showed that the zero-valent iron content of the material was 96.7%. 76.5mg of the material was added to 21.5mL of an aqueous solution containing 20mg / L hexavalent chromium and reacted for 24h under anaerobic conditions. The removal rate of hexavalent chromium by the material reached 98.9%. After the material was immersed in water for 60 days, the zero-valent iron content became 84.6%, and the decrease ratio was only 12.5%; under the same conditions, its removal rate of hexavalent chromium became 99.9%, and the increase ratio was 1.0%. Therefore, the 10% PSO-ZVI reducing material has good water stability and can maintain the reduction activity of hexavalent chromium for a long time.
[0036] Example 8 Preparation of surface modified micro-nano zero-valent iron material and its application in the degradation of hexavalent chromium
[0037] 5g of reduced iron powder and 2.5g of hexadecyltrimethoxysilane were mixed evenly in a 50ml ball mill, and placed in a planetary ball mill for 24h at 450rpm. The material was washed with anhydrous ethanol and vacuum dried for 12h to obtain a surface-modified micro-nano zero-valent iron material (50% PSO-ZVI). Scanning electron microscope (SEM) images showed that the particle size of the material was 527.5±49.1nm, and the results of the hydrogen production experiment showed that the zero-valent iron content of the material was 85.0%. 76.5mg of the material was added to 21.5mL of an aqueous solution containing 20mg / L hexavalent chromium and reacted for 24h under anaerobic conditions. The removal rate of hexavalent chromium by the material reached 94.2%. After the material was immersed in water for 60 days, the zero-valent iron content became 74.9%, and the decrease ratio was only 11.9%; under the same conditions, its removal rate of hexavalent chromium became 99.9%, and the increase ratio was 6.1%. Therefore, the 50% PSO-ZVI reduction material has good water stability and can maintain the reduction activity of hexavalent chromium for a long time.
[0038] Comparative Example 1 Preparation of ball-milled iron powder and its application in the degradation of trichloroethylene
[0039] 5g of reduced iron powder was added to a 50ml ball milling jar and placed in a planetary ball mill for 24h at a speed of 450rpm. The ball-milled iron powder was washed with anhydrous ethanol and vacuum dried for 12h to obtain ball-milled iron powder. The scanning electron microscope (SEM) image showed that the particle size of the ball-milled iron powder was 549.4±46.3nm. The results of the hydrogen production experiment showed that the zero-valent iron content of the ball-milled iron powder was 99.1%. 76.5mg of ball-milled iron powder was added to 21.5mL of an aqueous solution containing 10mg / L trichloroethylene and reacted under anaerobic conditions for 14 days. The removal rate of trichloroethylene by the ball-milled iron powder reached 34.5%. After soaking the ball-milled iron powder in water for 60 days, the zero-valent iron content became 47.6%, a decrease of 52.0%; under the same conditions, its removal rate of trichloroethylene became 8.0%, a decrease of 76.8%. Therefore, the experimental results show that the ball-milled iron powder without surface modification has poor stability in water and loses its activity in the reduction reaction of trichloroethylene due to agglomeration and passivation.
[0040] Comparative Example 2 Preparation of ball-milled iron powder and its application in the degradation of hexavalent chromium
[0041] 5g of reduced iron powder was added to a 50ml ball milling jar and placed in a planetary ball mill for 24h at 450rpm. The ball-milled iron powder was washed with anhydrous ethanol and vacuum dried for 12h to obtain the ball-milled iron powder. The scanning electron microscope (SEM) image showed that the particle size of the ball-milled iron powder was 549.4±46.3nm. The results of the hydrogen production experiment showed that the zero-valent iron content of the ball-milled iron powder was 99.1%. 76.5mg of ball-milled iron powder was added to 21.5mL of an aqueous solution containing 20mg / L hexavalent chromium and reacted for 24h under anaerobic conditions. The removal rate of hexavalent chromium by the ball-milled iron powder reached 57.9%. After the ball-milled iron powder was soaked in water for 60 days, the zero-valent iron content became 47.6%, a decrease of 52.0%; under the same conditions, its removal rate of hexavalent chromium became 25.6%, a decrease of 55.8%. Therefore, the experimental results show that the ball-milled iron powder without surface modification has poor stability in water and loses its reduction reaction activity for hexavalent chromium due to agglomeration and passivation.
[0042] The preparation method of the mechanochemical surface-modified micro-nano zero-valent iron in the present invention has low requirements on operation and equipment, can be prepared in batches, and has good market application prospects.
[0043] The contents specifically described above are illustrative rather than restrictive. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a zero-valent iron reducing material having micro-nano size and water stability, characterized in that: The following steps are involved: 1) mixing micron-sized zero-valent iron powder and hexadecyltrimethoxysilane, and performing mechanical ball milling; 2) Cleaning the material with a cleaning agent and drying it to obtain the zero-valent iron reduction material with micro-nano size and water stability.
2. The method for preparing a zero-valent iron reducing material having micro-nano size and water stability according to claim 1, characterized in that: The micron-grade zero-valent iron powder is reduced iron powder with a particle size ranging from 100 to 200 meshes.
3. The method for preparing a zero-valent iron reducing material having micro-nano size and water stability according to claim 1, characterized in that: The mass ratio of the micron-sized zero-valent iron powder to hexadecyltrimethoxysilane is 2:1 to 160:
1.
4. The method for preparing a zero-valent iron reducing material having micro-nano size and water stability according to claim 1, characterized in that: After the mechanical ball milling, the average particle size of the material is 269.0-527.5 nm.
5. The method for preparing a zero-valent iron reducing material having micro-nano size and water stability according to claim 1, characterized in that: The mechanical ball milling is performed using a ball mill, the ball milling speed is 400-500 rpm, and the ball milling time is 12-24 hours.
6. The method for preparing a zero-valent iron reducing material having micro-nano size and water stability according to claim 1, characterized in that: The cleaning agent is anhydrous ethanol.
7. The method for preparing a zero-valent iron reducing material having micro-nano size and water stability according to claim 1, characterized in that: The vacuum drying temperature is 60-80°C and the time is 12h-24h.
8. A zero-valent iron reducing material prepared according to the method according to any one of claims 1 to 7.
9. Use of the zero-valent iron reducing material according to claim 8 in degrading halogenated hydrocarbons or heavy metal pollutants in water.
Citation Information
Patent Citations
Hydrophobic inorganic powder material preparation method
CN107502003A
Preparation of ferromagnetic nanoparticle and application thereof in extraction and removal of micro-plastics
CN110237821A
Water-based magnetorheological fluids with wide operating temperature range and good viscosity stability
CN116344145A
Preparation method of mineral oil-based magnetorheological fluid
CN118725943A
Method for realizing synchronous micro-nano and stabilization of zero-valent iron based on silicic acid wet grinding process, product and application
CN118791113A
Cited By
Super-hydrophobic nano zero-valent iron modified material, and preparation method and application thereof
CN122517091A